New Comprehensive Clinical Classification of Dry Eye Syndrome Severity 2024. Part 1 - A. V. Trubilin; V. N. Trubilin; E. G. Poluninа; E. A. Kasparova (Oftalʹmologiâ)
Over the past ten years, the scientific ophthalmological community has shown a significant interest increase in studying dry eye syndrome (DES), as the number of such patients is steadily increasing every year. According to research conducted by the international DEWS working group, which studies DES, there is no single “gold standard” for diagnosing DES, as its manifestations are very diverse. A set of diagnostic tests is used to diagnose DES, reflecting both subjective and objective indicators of tear production. Subjective diagnostic criteria include questionnaires, the most widely used of which are the OSDI and SPEED questionnaires. It should be noted that these questionnaires characterize only subjective indicators and do not take into account objective criteria. In addition, the peculiarity of DES is that the presence of complaints is already a sign of this disease. However, the symptoms, namely the complaints of patients, do not always coincide with the clinical manifestations of dry eye syndrome — objective indicators of the state of tear production, such as the indicators of tear production tests. Based on modern concepts of the etiology and pathogenesis of dry eye syndrome, the state of the tear-producing system directly depends on the state of the tissues of the ocular surface — the conjunctiva, cornea and eyelids. Any inflammatory process affecting the tissues of the ocular surface leads to a violation of the stability of the tear film, its evaporation and an increase in osmolarity, which in turn causes an inflammatory process. Therefore, it is necessary in diagnosing dry eye syndrome to take into account a set of indicators characterizing the state of the tissues of the ocular surface, including the inflammatory process, in particular, conjunctival hyperemia, as well as the stability of the tear film, which depends primarily on its lipid component. The comprehensive clinical classification of dry eye syndrome presented in this article reflects not only objective indicators of impaired tear production and inflammation of the ocular surface, but also subjective indicators — quality of life according to the SPEED scale, characterizing the intensity and frequency of complaints of dryness and discomfort in the eyes. The above indicators allow to differentiate the severity of dry eye syndrome, which is of fundamental importance for choosing treatment methods and the volume of drug therapy, and assessing its effectiveness in dynamics. The developed diagnostic algorithm does not require special skills when carried out by a doctor, so it can be recommended for its use in wide ophthalmological practice.